Nanometer composite electrocatalyst and preparation method and application thereof

By coating the fluoroalkyl sulfonate on the electrocatalyst, the bubble barrier problem during the electrolytic water hydrogen production process is solved, and the energy conversion efficiency and stability are improved.

CN119877026APending Publication Date: 2025-04-25CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202311398347.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-25
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

During the process of electrolyzing hydrogen production, gas extraction reaction occurs between the two poles of the Yin and Yang, causing bubbles to adhere to the catalyst surface, hindering the contact between the catalyst and the reactants, resulting in low energy conversion efficiency and attenuation of the catalytic layer stability.

Method used

Nanocomposite electrocatalysts are used, which include an active metal and a conductive support supported by a supported active metal, and the catalyst surface is coated with a fluorine-containing alkyl sulfonate to alleviate the barrier to mass transfer of air bubbles.

Benefits of technology

It improves the energy conversion efficiency and stability in electrolyzed water, and reduces the cost of hydrogen production and equipment maintenance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119877026A_ABST
    Figure CN119877026A_ABST
Patent Text Reader

Abstract

The invention relates to a nano composite electrocatalyst as well as a preparation method and application thereof. The nano composite electrocatalyst comprises a catalyst and fluorine-containing alkyl sulfonate coating the catalyst, the catalyst comprises an active metal and a conductive carrier loading the active metal. The method disclosed by the invention is simple to operate, easy to control and mild in condition. The nano-composite electrocatalyst disclosed by the invention can relieve the problem of bubble mass transfer obstruction of a catalytic interface, and further improves the energy conversion efficiency and stability in electrolyzed water.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the technical field of nanomaterial preparation, and in particular, to a nanocomposite electrocatalyst and a preparation method and application thereof. Background Art

[0002] Energy and environmental issues are two major problems facing human development today. The current fossil fuel energy structure faces the dual crises of resource shortage and environmental sustainability. For many years, oil and coal reserves have been a concern for people, and the reserves available for long-term use in the future are very low. With the improvement of people's living standards, and because the use of fossil energy has caused environmental threats, damaged the human living environment and personal health, and is inconsistent with the sustainable development strategy, people have begun to pay active attention to environmental protection, energy use, and the development of new clean energy. The problem of developing new and available clean energy needs to be solved urgently.

[0003] Hydrogen production by water electrolysis is the main way to produce green hydrogen cleanly in the future. Compared with most mature traditional hydrogen production methods, water electrolysis hydrogen production technology has become the focus of current hydrogen production research and my country's energy strategic layout, relying on the advantages of renewable energy power generation, no pollution, no carbon emissions, high hydrogen purity, simple equipment and fast start and stop response. However, it has developed slowly due to the limitation of low energy conversion efficiency. During the electrolysis of water, gas evolution reactions occur at both the anode and cathode. The continuously generated bubbles are easy to adhere to the surface of the catalyst, blocking the contact between the catalyst and the reactants, causing the anode and cathode overpotentials to increase and performance fluctuations, resulting in reduced device energy conversion efficiency and catalyst layer stability attenuation, increasing hydrogen production costs and equipment maintenance costs. Especially under the operating conditions of commercial water electrolysis, with the increase of current density (usually 0.5-3A / cm 2 ), a large number of bubbles generated on the electrode surface will cause an overpotential of several hundred millivolts. If not discharged in time, a millimeter or even centimeter-level gas film will be formed, which will seriously hinder the continuation of the reaction. In addition, the surface bubbles and gas films will cover a considerable number of active sites, causing current or potential fluctuations, seriously affecting energy efficiency and component life. Summary of the invention

[0004] The purpose of the present disclosure is to provide a nanocomposite electrocatalyst and a preparation method and application thereof, wherein the nanocomposite electrocatalyst can alleviate the bubble mass transfer obstruction problem at the catalytic interface and further improve the energy conversion efficiency and stability in water electrolysis.

[0005] In order to achieve the above objectives, the present disclosure provides a nanocomposite electrocatalyst in a first aspect. The nanocomposite electrocatalyst comprises a catalyst and a fluorine-containing alkyl sulfonate coating the catalyst; the catalyst comprises an active metal and a conductive carrier supporting the active metal.

[0006] Optionally, the nanocomposite electrocatalyst is formed into particles; the average particle size of the nanocomposite electrocatalyst is 1 to 5 nm, and the BET specific surface area is 240 to 300 m 2 / g.

[0007] Optionally, the infrared spectrum of the nanocomposite electrocatalyst is between 531 and 537 cm -1 、620~623cm -1 1065~1070cm -1 1190~1195cm -1 and 1000~1210cm -1 There are characteristic peaks at each location.

[0008] Optionally, the carbon number of the alkyl group in the fluorinated alkyl sulfonate is 3 to 9, preferably potassium perfluorobutylsulfonate or potassium perfluorooctanesulfonate; the active metal is one of the precious metals, preferably platinum; and the conductive carrier is selected from one of carbon powder, titanium oxide and carbon nanotubes.

[0009] A second aspect of the present disclosure provides a method for preparing a nanocomposite electrocatalyst, the method comprising the following steps:

[0010] (1) first mixing an active metal source, an organic solvent, a fluorinated alkyl sulfonate and a conductive carrier to obtain a first mixed solution;

[0011] (2) allowing the reducing agent to contact and react with the first mixed solution in an air atmosphere, and drying the reaction product.

[0012] Optionally, in step (1), the mass ratio of the active metal source to the fluorinated alkyl sulfonate is 1:(0.5-5), preferably 1:(1-4); the mass ratio of the active metal source to the conductive carrier is 1:(0.5-4), preferably 1:(1-3);

[0013] The first mixing time is 0.5h to 5h, preferably 0.5 to 3h; the first mixing also includes being carried out under ultrasonic conditions, the ultrasonic time is 10 to 60min, preferably 20 to 40min; the ultrasonic power is 100 to 500W, preferably 100 to 300W.

[0014] Optionally, in step (1), the active metal source is selected from metal salts containing platinum, ruthenium and iridium, preferably a metal salt containing platinum, and further preferably one or more of chloroplatinic acid, sodium chloroplatinate and platinum acetylacetonate;

[0015] The organic solvent is selected from one or more of ethylene glycol, isopropanol and cyclohexane;

[0016] The conductive carrier is selected from one or more of carbon powder, titanium oxide and carbon nanotubes.

[0017] Optionally, step (1) further includes the following steps:

[0018] The active metal source and the organic solvent are mixed for a second time to obtain a second mixed solution; the fluorinated alkyl sulfonate is added to the second mixed solution for a third time to obtain a third mixed solution; the conductive carrier is added to the third mixed solution for the first time;

[0019] The second mixing includes mixing under stirring conditions, and the second mixing time is 5 to 30 minutes, preferably 5 to 15 minutes; the third mixing includes mixing under stirring conditions, and the third mixing time is 5 to 30 minutes, preferably 5 to 15 minutes.

[0020] Optionally, in step (2), the mass ratio of the reducing agent to the active metal source in step (1) is 1:(0.5-1.5), preferably 1:(0.9-1.1);

[0021] The contact reaction conditions include: temperature of 20 to 50°C, preferably 25 to 40°C, time of 1 to 5 hours, preferably 1 to 3 hours;

[0022] The reducing agent is selected from one or more of sodium borohydride, hexacarbonyl tungsten and hexadecanediol, preferably sodium borohydride;

[0023] The conditions of the drying treatment include: a drying temperature of 40 to 100° C., preferably 40 to 80° C., and a drying time of 1 to 10 hours, preferably 6 to 9 hours.

[0024] The third aspect of the present disclosure provides a nanocomposite electrocatalyst prepared by the method described in the second aspect of the present disclosure.

[0025] The fourth aspect of the present disclosure provides use of the nanocomposite electrocatalyst described in the first aspect of the present disclosure or the third aspect of the present disclosure in electrolysis of water.

[0026] Through the above technical scheme, the present invention specifically introduces fluorinated alkyl sulfonate as a surface coating agent during the synthesis of the nanocomposite electrocatalyst to obtain a composite electrocatalyst of fluorinated alkyl sulfonate coated catalyst. The method disclosed in the present invention is simple to operate, easy to control, and has mild conditions. The nanocomposite electrocatalyst disclosed in the present invention can alleviate the problem of bubble mass transfer obstruction at the catalytic interface and further improve the energy conversion efficiency and stability in electrolysis of water.

[0027] Other features and advantages of the present disclosure will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] The accompanying drawings are used to provide a further understanding of the present disclosure and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present disclosure but do not constitute a limitation of the present disclosure. In the accompanying drawings:

[0029] Figure 1 This is a low-resolution transmission electron microscope photograph of the nanocomposite electrocatalyst obtained in Example 1 of the present disclosure.

[0030] Figure 2 This is a low-resolution transmission electron microscope photograph of the nanocomposite electrocatalyst obtained in Comparative Example 1 of the present disclosure.

[0031] Figure 3 It is a comparison diagram of polarization curves of Example 1 of the present disclosure and Comparative Example 1.

[0032] Figure 4 This is a stability comparison chart between Example 1 and Comparative Example 1 of the present disclosure.

[0033] Figure 5 This is an infrared comparison diagram of Example 1 and Comparative Example 1 of the present disclosure. DETAILED DESCRIPTION

[0034] The specific implementation of the present disclosure is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described herein is only used to illustrate and explain the present disclosure, and is not used to limit the present disclosure.

[0035] In a first aspect, the present disclosure provides a nanocomposite electrocatalyst, wherein the nanocomposite electrocatalyst comprises a catalyst and a fluorine-containing alkyl sulfonate coating the catalyst; the catalyst comprises an active metal and a conductive carrier supporting the active metal.

[0036] The surface of the nanocomposite electrocatalyst disclosed in the present invention is modified by a fluorinated alkyl sulfonate organic molecular layer, which is helpful to alleviate the problem of bubble mass transfer obstruction at the catalytic interface.

[0037] According to one embodiment of the present disclosure, the nanocomposite electrocatalyst is formed into particles; the average particle size of the nanocomposite electrocatalyst is 1 to 5 nm, preferably 2 to 4 nm; the BET specific surface area is 240 to 300 m 2 / g, preferably 250 to 280 m 2 / g.

[0038] According to one embodiment of the present disclosure, the infrared spectrum of the nanocomposite electrocatalyst is between 531 and 537 cm -1 、620~623cm -1 1065~1070cm -1 1190~1195cm -1 and 1000~1210cm-1 There are characteristic peaks at each location.

[0039] According to an embodiment of the present disclosure, the carbon number of the alkyl group in the fluorinated alkyl sulfonate is 3 to 9, preferably potassium perfluorobutyl sulfonate or potassium perfluorooctane sulfonate; the active metal is one of the noble metals, preferably platinum; the conductive carrier is selected from one of carbon powder, titanium oxide and carbon nanotubes. The above preferred embodiment is conducive to alleviating the bubble mass transfer barrier at the catalytic interface.

[0040] A second aspect of the present disclosure provides a method for preparing a nanocomposite electrocatalyst, the method comprising the following steps:

[0041] (1) first mixing an active metal source, an organic solvent, a fluorinated alkyl sulfonate and a conductive carrier to obtain a first mixed solution;

[0042] (2) allowing the reducing agent to contact and react with the first mixed solution in an air atmosphere, and drying the reaction product.

[0043] The nanocomposite electrocatalyst obtained by the method disclosed in the present invention is in the form of nanoparticles, with complete morphology, uniform particle size and good dispersibility. The method is simple to operate, mild in conditions, green, energy-saving and safe, and suitable for large-scale production. The nanocomposite electrocatalyst disclosed in the present invention can remove fluorinated alkyl sulfonates and be applied to catalytic reactions; in some systems, specific fluorinated alkyl sulfonate molecules affect the performance of the internal nanocatalyst surface through intermolecular interactions, changes in hydrophilicity and hydrophobicity, and pore regulation.

[0044] According to an embodiment of the present disclosure, in step (1), the mass ratio of the active metal source to the fluorinated alkyl sulfonate is 1: (0.5-5), preferably 1: (1-4); the mass ratio of the active metal source to the conductive carrier is 1: (0.5-4), preferably 1: (1-3); the first mixing time is 0.5h-5h, preferably 0.5-3h; the first mixing also includes being carried out under ultrasonic conditions, the ultrasonic time is 10-60min, preferably 20-40min; the ultrasonic power is 100-500W, preferably 100-300W. The above preferred embodiments are conducive to alleviating the bubble mass transfer obstruction at the catalytic interface.

[0045] According to an embodiment of the present disclosure, in step (1), the active metal source is selected from metal salts containing platinum, ruthenium and iridium, preferably metal salts containing platinum, and more preferably one or more of chloroplatinic acid, sodium chloroplatinate and platinum acetylacetonate; the organic solvent is selected from one or more of ethylene glycol, isopropanol and cyclohexane; the conductive carrier is selected from one or more of carbon powder, titanium oxide and carbon nanotubes. The above preferred embodiment is conducive to alleviating the bubble mass transfer barrier at the catalytic interface.

[0046] According to an embodiment of the present disclosure, in step (2), the mass ratio of the reducing agent to the active metal source in step (1) is 1: (0.5-1.5), preferably 1: (0.9-1.1); the conditions of the contact reaction include: the temperature is 20-50°C, preferably 25-40°C, the time is 1-5h, preferably 1-3h; the reducing agent is selected from one or more of sodium borohydride, hexacarbonyl tungsten and hexadecanediol, preferably sodium borohydride; the conditions of the drying treatment include: the drying temperature is 40-100°C, preferably 40-80°C, and the drying time is 1-10h, preferably 6-9h. The above preferred embodiment is conducive to alleviating the bubble mass transfer barrier at the catalytic interface.

[0047] According to an embodiment of the present disclosure, step (1) further includes the following steps: performing a second mixing of the active metal source and the organic solvent to obtain a second mixed solution; adding the fluorinated alkyl sulfonate to the second mixed solution and performing a third mixing to obtain a third mixed solution; adding the conductive carrier to the third mixed solution to perform the first mixing; the second mixing includes performing the second mixing under stirring conditions, and the second mixing time is 5 to 30 minutes, preferably 5 to 15 minutes; the third mixing includes performing the third mixing under stirring conditions, and the third mixing time is 5 to 30 minutes, preferably 5 to 15 minutes. The above preferred embodiments are conducive to alleviating the bubble mass transfer obstruction at the catalytic interface.

[0048] The third aspect of the present disclosure provides a nanocomposite electrocatalyst prepared by the method described in the second aspect of the present disclosure.

[0049] The fourth aspect of the present disclosure provides use of the nanocomposite electrocatalyst described in the first aspect of the present disclosure or the third aspect of the present disclosure in electrolysis of water.

[0050] The present invention is further illustrated by the following examples, but the present invention is not limited thereto.

[0051] Unless otherwise specified, the raw materials used in the following examples and comparative examples were commercially available.

[0052] In the present disclosure, the scanning electron microscope was tested on a Zeiss Supra 55 instrument.

[0053] BET test method: In the present disclosure, the pore structure properties of the samples were measured by a Quantachrome AS-6B analyzer, and the specific surface area of ​​the catalyst was obtained by the Brunauer-Emmett-Taller (BET) method.

[0054] Infrared spectroscopy (IR) was performed using a Thermo ScientificTM Nicolet TM The iS50 FTIR instrument was tested.

[0055] The electrochemical performance was tested on a VersaSTAT4 instrument.

[0056] Example 1

[0057] (1) 15 mL of ethylene glycol and 20.5 mg of H2PtCl6·6H2O (20.5 mg) were added to a conical flask and stirred for 10 minutes to disperse evenly to obtain a second mixed solution. The second mixed solution was light yellow;

[0058] Weigh 50 mg of potassium perfluorobutanesulfonate (FC-98) and dissolve it in the second mixed solution, and stir for 10 minutes to obtain a uniform third mixed solution;

[0059] 30 mg of Vulcan XC-72 carbon powder was weighed and added to the third mixed solution, the mixture was stirred for 10 minutes, and ultrasonically dispersed for 30 minutes at a power of 200 W to obtain a first mixed solution;

[0060] The mass ratio of the active metal source to the fluorinated alkyl sulfonate is 1:2.44; the mass ratio of the active metal source to the conductive carrier is 1:1.46.

[0061] (2) Weigh 20 mg of sodium borohydride (NaBH4) and dissolve it in 5 ml of water. Use a syringe to slowly inject the aqueous solution into the first mixed solution in an air atmosphere at 30°C, and further stir for 2 hours, wherein the mass ratio of the reducing agent to the active metal source in step (1) is 1:1.03; after stirring, centrifuge and discard the supernatant, repeat the centrifugation process twice, filter after centrifugation, and dry the black powder obtained by filtration in a vacuum drying oven at 60°C for 6 hours to obtain a Pt / C composite electrocatalyst E1 with a composite interface.

[0062] Example 2

[0063] (1) 10 mL of ethylene glycol and 10 mg of H2PtCl6·6H2O (10 mg) were added to a conical flask and stirred for 10 minutes to disperse evenly to obtain a second mixed solution. The second mixed solution was light yellow;

[0064] Weigh 40 mg of potassium perfluorobutanesulfonate (FC-98) and dissolve it in the second mixed solution, and stir for 10 minutes to obtain a uniform third mixed solution;

[0065] Weigh 20 mg of Vulcan XC-72 carbon powder and add it to the third mixed solution. Stir the mixture for 10 minutes and perform ultrasonic dispersion for 20 minutes at a power of 200 W to obtain a first mixed solution.

[0066] The mass ratio of the active metal source to the fluorinated alkyl sulfonate is 1:4; the mass ratio of the active metal source to the conductive carrier is 1:2.

[0067] (2) Weigh 10 mg of sodium borohydride (NaBH4) and dissolve it in 5 ml of water. Use a syringe to slowly inject the aqueous solution into the first mixed solution in an air atmosphere at 30°C, and further stir for 1 hour, wherein the mass ratio of the reducing agent to the active metal source in step (1) is 1:1; after stirring, centrifuge and discard the supernatant, repeat the centrifugation process twice, filter after centrifugation, and dry the black powder obtained by filtration in a vacuum drying oven at 40°C for 6 hours to obtain a Pt / C composite electrocatalyst E2 with a composite interface.

[0068] Example 3

[0069] (1) 20 mL of ethylene glycol and 30 mg of H2PtCl6·6H2O (30 mg) were added to a conical flask and stirred for 10 minutes to disperse evenly to obtain a second mixed solution. The second mixed solution was light yellow;

[0070] Weigh 60 mg of potassium perfluorobutanesulfonate (FC-98) and dissolve it in the second mixed solution, and stir for 10 minutes to obtain a uniform third mixed solution;

[0071] Weigh 40 mg of Vulcan XC-72 carbon powder and add it into a conical flask, stir the mixture for 10 minutes, and ultrasonically disperse it for 40 minutes at a power of 200 W to obtain a first mixed solution;

[0072] The mass ratio of the active metal source to the fluorinated alkyl sulfonate is 1:2; the mass ratio of the active metal source to the conductive carrier is 1:3.

[0073] (2) Weigh 30 mg of sodium borohydride (NaBH4) and dissolve it in 10 ml of water. Use a syringe to slowly inject the aqueous solution into the first mixed solution in an air atmosphere at 30°C, and further stir for 3 hours, wherein the mass ratio of the reducing agent to the active metal source in step (1) is 1:1; after the stirring is completed, centrifuge and discard the supernatant. Repeat the centrifugation process twice, filter after centrifugation, and dry the black powder obtained by filtration in a vacuum drying oven at 80°C for 6 hours to obtain a Pt / C composite electrocatalyst E3 with a composite interface.

[0074] Example 4

[0075] The method of Example 4 is the same as that of Example 1, except that in step (1), 100 mg of potassium perfluorobutanesulfonate (FC-98) is weighed, and the mass ratio of the active metal source to the fluorinated alkyl sulfonate is 1:5.

[0076] (1) 15 mL of ethylene glycol and 20 mg of H2PtCl6·6H2O were added to a conical flask and stirred for 10 minutes to disperse evenly to obtain a second mixed solution. The second mixed solution was light yellow;

[0077] Weigh 100 mg of potassium perfluorobutanesulfonate (FC-98) and dissolve it in the second mixed solution, and stir for 10 minutes to obtain a uniform third mixed solution;

[0078] 30 mg of Vulcan XC-72 carbon powder was weighed and added to the third mixed solution, the mixture was stirred for 10 minutes, and ultrasonically dispersed for 30 minutes at a power of 200 W to obtain a first mixed solution;

[0079] The mass ratio of the active metal source to the fluorinated alkyl sulfonate is 1:5; the mass ratio of the active metal source to the conductive carrier is 1:1.46.

[0080] (2) Weigh 20 mg of sodium borohydride (NaBH4) and dissolve it in 5 ml of water. Use a syringe to slowly inject the aqueous solution into the first mixed solution in an air atmosphere at 30°C, and further stir for 2 hours, wherein the mass ratio of the reducing agent to the active metal source in step (1) is 1:1.03; after the stirring is completed, centrifuge and discard the supernatant. Repeat the centrifugation process twice, filter after centrifugation, and dry the black powder obtained by filtration in a vacuum drying oven at 60°C for 6 hours to obtain a Pt / C composite electrocatalyst E4 with a composite interface.

[0081] Comparative Example 1

[0082] (1) 15 mL of ethylene glycol and 20.5 mg of H2PtCl6·6H2O (20.5 mg) were added to a conical flask and stirred for 10 minutes to disperse evenly to obtain a second mixed solution. The second mixed solution was light yellow;

[0083] Weigh 30 mg of Vulcan XC-72 carbon powder and add it to the second mixed solution. Stir the mixture for 10 minutes and disperse it by ultrasound for 30 minutes at a power of 200 W to obtain a first mixed solution.

[0084] Wherein, the mass ratio of the active metal source to the conductive carrier is 1:1.46.

[0085] (2) Weigh 20 mg of sodium borohydride (NaBH4) and dissolve it in 5 ml of water. Use a syringe to slowly inject the aqueous solution into the first mixed solution in an air atmosphere at 30°C, and further stir for 2 hours, wherein the mass ratio of the reducing agent to the active metal source in step (1) is 1:1.03; after stirring, centrifuge and discard the supernatant, repeat the centrifugation process twice, filter after centrifugation, and dry the black powder obtained by filtration in a vacuum drying oven at 60°C for 6 hours to obtain electrocatalyst D1.

[0086] Comparative Example 2

[0087] S1. Dissolve 50 mg of potassium perfluorobutanesulfonate (FC-98) in 1 ml of ethylene glycol and stir for 10 minutes to form a mixed solution;

[0088] S2. The mixed solution in S1 is coated on the surface of the electrocatalyst D1 obtained in Comparative Example 1, and then dried in a vacuum drying oven at 60° C. for 6 hours to obtain the electrocatalyst D2.

[0089] Test Example 1

[0090] The composite electrocatalysts obtained in Examples 1 to 4 and Comparative Examples 1 to 2 were tested by SEM, IR and BET specific surface area. The results are shown in Tables 1 and Figure 5 .

[0091] Table 1

[0092]

[0093] like Figure 5 As shown, in Figure 5 (b) 1192.30cm -1 、1068.80cm -1 、622.21cm -1 and 535.39cm -1 The absorption peaks of different intensities appearing on the left and right are mainly attributed to the sulfonic acid groups in fluorinated alkyl sulfonates; -1 The peaks in the range are the stretching vibration peaks of CF, which mainly come from the CF bonds of fluorinated alkyl sulfonate FC-98; in addition, the composite electrocatalyst still has Figure 5 (b) shows the infrared characteristic peaks, which indicates that the obtained catalyst is not a simple mechanical combination of organic layer and inorganic layer, and there is a strong adsorption force between platinum and sulfonic acid groups.

[0094] Test Example 2

[0095] The composite electrocatalysts obtained in Examples 1 to 4 and Comparative Examples 1 to 2 were tested for their gas repellency. The specific testing method was as follows: a high-speed camera (model X-Motion, AOS Technologies) was used to photograph the bubble contact angle. The sample to be tested was horizontally fixed in a 0.5MH2SO4 solution, and then a 2μL bubble was injected directly below the electrode using a bent needle to photograph the bubble contact angle. When photographing the gas evolution reaction, the sample to be tested was vertically fixed in a square transparent electrolytic cell, and a three-electrode system was used for electrochemical control so that the reaction current was 100mA. The bubble contact angle represents the difficulty of bubbles detaching from the electrode surface. The test results are shown in Table 2.

[0096] Table 2

[0097]

[0098] According to the data in Table 2, the composite electrocatalyst disclosed in the present invention has a larger bubble contact angle than that of Comparative Examples 1 to 2, indicating that the gas repellency of the composite electrocatalyst disclosed in the present invention is improved, and the bubbles can detach from the electrode surface faster, thereby contacting with fresh electrolyte more quickly to generate new reactions, thereby improving bubble mass transfer and promoting reactions.

[0099] Test Example 3

[0100] The electrochemical test was performed using VersaSTAT4. The composite electrocatalysts obtained in Examples 1 to 4 and Comparative Examples 1 to 2 were used as catalysts, respectively, and were prepared into a uniformly dispersed slurry and then dropped onto a designated area (S = 1 × 1 cm) of the cut double hydrophilic carbon paper. 2 ), using carbon paper fixed by electrode clamp as working electrode. The electrolyte is 0.5MH2SO4 saturated with argon gas, and the catalyst loading is 0.4mg / cm 2 , the workstation potential was set to -0.8 V ~ 0 V (relative to SCE), and the scan rate was 0.05 V / s.

[0101] In addition, comparative example 3 is set for comparison. In comparative example 3, the composite electrocatalyst D1 obtained in comparative example 1 is used as a catalyst, and a uniformly dispersed slurry is prepared and then dripped onto a designated area (S=1×1 cm) of the cut double hydrophilic carbon paper. 2 ), using carbon paper fixed by an electrode clamp as the working electrode; the electrolyte was a newly prepared argon-saturated 0.5M H2SO4, and 50mg potassium perfluorobutanesulfonate (FC-98) was added to the electrolyte, with a catalyst loading of 0.4mg / cm 2 , the workstation potential was set to -0.8 V ~ 0 V (relative to SCE), and the scan rate was 0.05 V / s.

[0102] Table 3

[0103]

[0104]

[0105] According to the data in Table 3, in HER, at -0.52V vs. RHE, the current density of the composite electrocatalyst disclosed in the present invention is higher, and the performance decay is less after the same number of cyclic voltammetry tests. By comparing Example 1 with Comparative Example 1, it can be seen that the current density of the composite electrocatalyst disclosed in the present invention is increased by about 12% at the same voltage. By comparing Example 1 with Example 4, it can be seen that within the preferred mass ratio range of the active metal source to the fluorinated alkyl sulfonate disclosed in the present invention, the current density of the composite electrocatalyst is higher at the same voltage, and the performance decay is less after the same number of cyclic voltammetry tests.

[0106] The preferred embodiments of the present disclosure are described in detail above in conjunction with the accompanying drawings; however, the present disclosure is not limited to the specific details in the above embodiments. Within the technical concept of the present disclosure, a variety of simple modifications can be made to the technical solution of the present disclosure, and these simple modifications all fall within the protection scope of the present disclosure.

[0107] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present disclosure will not further describe various possible combinations.

[0108] In addition, various embodiments of the present disclosure may be arbitrarily combined, and as long as they do not violate the concept of the present disclosure, they should also be regarded as the contents disclosed by the present disclosure.

Claims

1. A nanocomposite electrocatalyst, characterized in that: The nanocomposite electrocatalyst comprises a catalyst and a fluorine-containing alkyl sulfonate coating the catalyst; the catalyst comprises an active metal and a conductive carrier supporting the active metal.

2. The nanocomposite electrocatalyst according to claim 1, wherein The nanocomposite electrocatalyst is formed into particles; the average particle size of the nanocomposite electrocatalyst is 1 to 5 nm, and the BET specific surface area is 240 to 300 m 2 / g.

3. The nanocomposite electrocatalyst according to claim 1, wherein The infrared spectrum of the nanocomposite electrocatalyst is between 531 and 537 cm -1 、620~623cm -1 1065~1070cm -1 1190~1195cm -1 and 1000~1210cm -1 There are characteristic peaks at each location.

4. The nanocomposite electrocatalyst according to claim 1, wherein The carbon number of the alkyl group in the fluorinated alkyl sulfonate is 3 to 9, and the fluorinated alkyl sulfonate is preferably potassium perfluorobutyl sulfonate or potassium perfluorooctane sulfonate; the active metal is one of the precious metals, preferably platinum; the conductive carrier is selected from one of carbon powder, titanium oxide and carbon nanotubes.

5. A method for preparing a nanocomposite electrocatalyst, characterized in that: The method comprises the following steps: (1) first mixing an active metal source, an organic solvent, a fluorinated alkyl sulfonate and a conductive carrier to obtain a first mixed solution; (2) allowing the reducing agent to contact and react with the first mixed solution in an air atmosphere, and drying the reaction product.

6. The method according to claim 5, wherein: In step (1), the mass ratio of the active metal source to the fluorinated alkyl sulfonate is 1:(0.5-5), preferably 1:(1-4); the mass ratio of the active metal source to the conductive carrier is 1:(0.5-4), preferably 1:(1-3); The first mixing time is 0.5h to 5h, preferably 0.5 to 3h; the first mixing also includes being carried out under ultrasonic conditions, the ultrasonic time is 10 to 60min, preferably 20 to 40min; the ultrasonic power is 100 to 500W, preferably 100 to 300W.

7. The method according to claim 5, wherein: In step (1), the active metal source is selected from metal salts containing platinum, ruthenium and iridium, preferably a metal salt containing platinum, and more preferably one or more of chloroplatinic acid, sodium chloroplatinate and platinum acetylacetonate; The organic solvent is selected from one or more of ethylene glycol, isopropanol and cyclohexane; The conductive carrier is selected from one or more of carbon powder, titanium oxide and carbon nanotubes.

8. The method according to claim 5, wherein: Step (1) also includes the following steps: The active metal source and the organic solvent are mixed for a second time to obtain a second mixed solution; the fluorinated alkyl sulfonate is added to the second mixed solution and mixed for a third time to obtain a third mixed solution; adding the conductive carrier to the third mixed solution to perform the first mixing; The second mixing includes mixing under stirring conditions, and the second mixing time is 5 to 30 minutes, preferably 5 to 15 minutes; the third mixing includes mixing under stirring conditions, and the third mixing time is 5 to 30 minutes, preferably 5 to 15 minutes.

9. The method according to claim 5, wherein: In step (2), the mass ratio of the reducing agent to the active metal source in step (1) is 1:(0.5-1.5), preferably 1:(0.9-1.1); The contact reaction conditions include: temperature of 20 to 50°C, preferably 25 to 40°C, time of 1 to 5 hours, preferably 1 to 3 hours; The reducing agent is selected from one or more of sodium borohydride, hexacarbonyl tungsten and hexadecanediol, preferably sodium borohydride; The conditions of the drying treatment include: a drying temperature of 40 to 100° C., preferably 40 to 80° C., and a drying time of 1 to 10 hours, preferably 6 to 9 hours.

10. The nanocomposite electrocatalyst prepared by the method according to any one of claims 5 to 9.

11. Use of the nanocomposite electrocatalyst according to any one of claims 1 to 4 or claim 10 in electrolysis of water.

Citation Information

Patent Citations

  • Bubble adhesion preventing coating with ion conduction function and preparation method thereof

    CN111074296A

  • Electrolyte for electrolyzing water and system for producing hydrogen by electrolyzing water

    CN111101143A

  • Preparation method of membrane electrode for electrolyzing water by proton exchange membrane

    CN112176361A

  • Water electrolysis hydrogen production proton exchange membrane electrode and preparation method

    CN113957472A

  • Carbon carrier for fuel cell and preparation and application of platinum-based catalyst of carbon carrier

    CN116598515A